A Competing Risk Analysis of Women Dying of Maternal, Infectious, or Non-Communicable Causes in the Kintampo Area of Ghana - Abubakari, Sulemana Watara; Badasu, Delali Margaret; Apraku, Edward Anane; Amenga-Etego, Seeba; Asante, Kwaku Poku; Bawah, Ayaga Agula; Owusu-Agyei, Seth (Frontiers in Global Women's Health, 2021)
Background: Maternal, infectious, and non-communicable causes of death combinedly are a major health problem for women of reproductive age (WRA) in sub-Saharan Africa (SSA). Little is known about the relative risks of each of these causes of death in their combined form and their demographic impacts. The focus of studies on WRA has been on maternal health. The evolving demographic and health transitions in low- and middle-income countries (LMICs) suggest a need for a comprehensive approach to resolve health challenges of women beyond maternal causes. Methods: Deaths and person-years of exposure (PYE) were calculated by age for WRA within 15–49 years of age in the Kintampo Health and Demographic Surveillance System (KHDSS) area from January 2005 to December 2014. Causes of death were diagnosed using a standard verbal autopsy questionnaire and the 10th Revision of the International Statistical Classification of Diseases and Related Health Problems (ICD-10). Identified causes of death were categorized into three broad areas, namely, maternal, infectious, and non-communicable diseases. Multiple decrements and associated single decrement life table methods were used. Results: Averting any of the causes of death was seen to lead to improved life expectancy, but eliminating infectious causes of death leads to the highest number of years gained. Infectious causes of death affected all ages and the gains in life expectancy, assuming that these causes were eliminated, diminished with increasing age. The oldest age group, 45–49, had the greatest gain in reproductive-aged life expectancy (RALE) if maternal mortality was eliminated. Discussion: This study demonstrated the existence of a triple burden. Infectious causes of death are persistently high while deaths from non-communicable causes are rising and the level of maternal mortality is still unacceptably high. It recommends that attention should be given to all the causes of death among WRA.